ANALISIS FRAMING ROBERT N. ENTMAN PADA MEDIA ONLINE KOMPAS.COM TENTANG PEMBERITAAN TEWASNYA BRIGADIR J - Fahrika Tri Ramadhanti; Andri Maijar (KINEMA: Jurnal Komunikasi dan Penyiaran, 2023)
The subject matter of this thesis is the occurrence of a shootout among police officers at the home of Inspector General Ferdy sambo due to alleged harassment of his wife then became the news of all journalism platforms with various forms of processing by the media, so to identify the use of Robert N. Entman's framing analysis on KOMPAS.com online media related to the news of the death of "Brigadier J" with four elements, Define Problem, Diagnose Causes, Make Moral Judgement, Treatment Recommendation. The purpose of this writing is to identify the framing of Robert N. Entman's Framing Analysis on Kompas.com Online Media Regarding the News of the Death of "Brigadier J" with descriptive qualitative research methods so as to help describe Entman's framing on the news and data collection found from written archives on the KOMPAS.com online media portal related to the news. The research results of the news findings of 390 pieces of news categorized into 42 pieces of news on the victim's side, 125 pieces of news on the police side, and 223 pieces of news on third parties show that there is a tendency for KOMPAS.com online media not to linger on the time of revealing the chronology of the death of "Brigadier J". Then based on the framing identified on KOMPAS.com online media, it also takes many perspectives from third parties both in government institutions and independent institutions. This online media is quite balanced in informing related to the death of "Brigadier J".Kata kunci: Analisis framing, Model Robert N. Entman, Berita, Tewasnya ÔÇ£Brigadir JÔÇØ